Gjellestad and other centres of power in Vingulmǫrk - Christian Løchsen Rødsrud (Viking)
This chapter addresses the centre of power at Gjellestad through a comparative approach to other power centres – in the form of large manorial farms – in the region of Vingulmǫrk. Centres are areas with special position and function within a society and are identified through the plotting of elite indicators, including mound size, aristocratic settlement structures (halls or other large buildings), objects made of precious materials (gold), weapons, and imported objects. By mapping all these categories, it becomes evident that Gjellestad did not exist in solitude, but rater in relation to several other centres. Ten clusters, indicating centres of political power, are identified, and six of them are placed along the coast at regular intervals. The clusters show that the centres are in continuous use, but they also paint a dynamic picture with fluctuations and alternations in the marking of power over time. Gjellestad stands out as a latecomer, growing to prominence in the period 400-550 AD, and later reinforced by the ship burial in the early Viking Age.